Experimental Study on the Effects of Methanol and Ethanol on Gasoline Engine Performance and Exhaust Emissions / M. S. M. Zaharin...[et al.] - M. S., M. Zaharin; N. R., Abdullah; Dahalan, M. Imran; Sharudin, Hazim; A.R., Asiah; M., Beriache (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Increasing demands of energy sources in automotive sector have led to depletion of fossil fuels. In solving the problem of fuel supply, researchers have rapidly raised intentions on alternative fuels since the late 20th century, in which it is highly favourable over gasoline fuel due to its cost-efficiency and environmental friendly. This paper presented the effects of various alcohol-gasoline blends on engine performance and exhaust emissions. Four fuel blends; M5 (methanol 5% + pure gasoline 95%), M15 (methanol 15% + pure gasoline 85%), E5 (ethanol 5% + pure gasoline 95%) and E15 (ethanol 15% + pure gasoline 85%) were tested on a 4-cylinder, 4-strokes, 1.6L natural aspirated spark ignition (SI) engine under condition of wide open throttles and engine speed varied from 1000-4000 rpm. The results showed that methanol and ethanol fuels provide air-fuel charge cooling to increase the density of the charge. Thus, the fuel blends produced higher engine brake power than that of pure gasoline. In relation to brake specific fuel consumption (BSFC), E15 presented the highest result due to the lower energy content compared to that of other blends. Brake thermal efficiency (BTE) produced by M15 was the highest, obtaining 5.17% increment from pure gasoline compared to other fuel blends which were 1.6%, 1.16% and 2.47% for M5, E5 and E15, respectively. The fuel blends emitted lower exhaust emissions of carbon monoxide (CO) and hydrocarbon (HC) gases due to the addition of oxygenated fuel that promoted better combustion process and reduced exhaust emissions of CO and HC. However, the blends have resulted in increase of NOx emissions in comparison to that of pure gasoline which can be attributed to the higher flame temperature of alcohol. Optimized blend ratios for methanol and ethanol with gasoline were found to be better than pure gasoline fuel in terms of fuel properties, combustion behaviour, engine performance and exhaust emissions with E15 producing the highest engine brake power of 60.3 kW and emitting the lowest CO and HC emissions at high engine speed with 0.566% and 114.2 ppm, respectively. Meanwhile, M15 provided the most thermal efficient fuel blend at all operating conditions.